Genômica comparativa e filogeográfica em espécies do gênero Atta (HYMENOPTERA: FORMICIDAE) - Barbosa, Josefa Tatiana de Souza (2018)
Leaf-cutting ants of the genus Atta are widely distributed throughout the Neotropical Region, being important pests of agricultural and forest crops. In Brazil, they are distributed throughout the national territory. The species Atta opaciceps Borgmeier, 1939 is especially distributed in the Northeast of the country, covering the Caatinga and Atlantic Forest Biomes. The objective of this work was to sequence four complete mitochondrial genomes for the species A. opaciceps, A. colombica, A. texana and A. sexdens rubropilosa and to analyze the population structure of A. opaciceps using cytochrome oxidase I subunit (COI) sequences. In the assemblage of the genome, the reads for the species A. opaciceps were obtained from the sequencing, whereas for the other species the reads were obtained from the NCBI. For the assembly of the genomes, the reads of the four species were mapped using the mitochondrial genome of A. laevigata as reference and Geneious software for the phylogenetic analyzes. The analyzes for the intergenic spaces showed that in Atta they are larger than outside the group, concluding that Atta mitogenomas are characterized by a high conservation in the order and organization of the genes. For a phylogeographic approach based on the mitochondrial COI gene, 11 collection points were sampled for the A. opaciceps species distributed in the Northeast Region with two Biomes (Caatinga and Mata Atlântica). It was also estimated the phylogeographic grouping using Bayesian analysis and modeling of climatic niches thus identifying five haplotypes distributed throughout the geographic region. Revealing that the Caatinga and Atlantic Forest Biomes did not influence the modeling of the populations of A. opaciceps, and suggests that the species has a wide dispersion and adaptation capacity to the different Biomes.